Gestão de operações de serviços de emergência no contexto de cidades inteligentes e sustentáveis: o caso da Polícia Militar do Paraná - Oliveira, Vanessa Alves Tonete (2020)
Projecting population growth will be a challenge for municipal managers. Smart and sustainable cities are a way to improve citizen services and quality of life, including public safety. In this context, the objective of this study was to analyze and propose improvements in the service management 190 in the Military Police, in the context of smart and sustainable cities, using Pato Branco-PR as a case study. For this, the operations management of the 190 services at the Military Police was diagnosed, through semi-structured interviews and content analysis with Military Police managers and mapping of the service process. In addition, a multicriteria decision support model was developed and tested to prioritize event handling in the call center 190, using the AHP and TOPSIS 2-Tuple methods. The results suggest that the concepts of smart and sustainable service and city operations management are related and that local police contribute to city intelligence. Thus, some actions may broaden this scope, such as technical issues, such as the integration of police systems and the implementation of facial recognition, contributing to the availability of information more easily and quickly. In addition, the multicriteria decision support model for prioritization of occurrences, the AHP method allowed the weighting of the criteria from the experts, the TOPSIS 2-tuple method allowed the classification of alternatives related to the information that the citizen passes to the attendant, and AHP proved to be effective in weighing the options of possible responses within the alternatives. Thus, it was possible to simulate occurrences with data of occurrences already attended by the Military Police, in which each information contained a value previously obtained from the specialists, and in the end the severity value of the occurrence was obtained, being 1 less severe and 10 the highest value, which was obtained based on the FMEA severity scale. Thus, the police officer responsible for the decision, in cases where there are two or more occurrences, has his decision obtained with the help of the expert system.